The Problems of Contested Divorce in Marriages Over 30 Years Old at the Pangkalan Balai Religious Court - Armasito Armasito; Rafida Ramelan; Sulistiawati AR (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2024)
This research was motivated by the problem of contested divorce in marriages over 30 years old, which means that the husband and wife ended their marital relationship after many years of marriage. At that age, they would likely already have children or even grandchildren. This indicates that the couple's household is not in line with the goal of marriage, which is to build a happy and eternal family. This research aims to identify the problems and considerations of judges in deciding cases of contested divorce when the marriage is over 30 years old. The type of research used is field research, using data collection techniques through interviews, documentation, and literature. Interviews were conducted using an interview guide in the form of a list of questions to be asked of the judges. The data analysis technique uses qualitative descriptive methods. Based on the results of research conducted at the Pangkalan Balai Religious Court through interviews with judges show that the factors causing contested divorce in marriages over 30 years old are the husband's irresponsibility as head of the family, the husband having an affair/having another dream woman, committing domestic violence, continuous disputes, and leaving the wife. Meanwhile, in deciding cases of contested divorce when the marriage is over 30 years old, the judge considers it based on procedures that meet the requirements and the firm wishes of the parties and considers the benefit.